The role of the guanine nucleotide exchange factor Rab3GEP in the regulation of Rab27a - Sanzà, Paolo (2017)
In mammalian cells vesicle transport is an important process, many diseases are caused by defects of trafficking. Key elements for organelle trafficking are Rab proteins which regulate this system. Rabs are GTPases and belong to the Ras superfamily proteins. Rab27a is one of the main actors of this process, it promotes the recruitment of secretory vesicles at the release site, the plasma membrane, by its role of interconnection between the vesicle and the motor protein myosin V. Dysfunction leads to disease such as Griscelli syndrome. Rab27a is a molecular switch, in the active state is able to bind effectors. The switching from the GDP-bound to the GTP-bound is catalysed by Rab3GEP. Furthermore, to function properly Rab27a has to be targeted to the organelle membrane, this function has been attributed to the guanine exchange factor as well. Rab3GEP contains a DENN domain (differentially expressed in normal versus neoplastic) at the N-terminus and a death domain at the C-terminus. Rab3GEP belongs to the family of DENN domain proteins, in general DENN domains are considered as domains with a guanine exchange factor activity. Down-regulation of this Rab3GEP in melan-a melanocytes induces to melanosome clustering at the perinuclear area. There is no knowledge about the mechanism of Rab3GEP in the activation and targeting of Rab27a to the vesicle membranes. To better characterise Rab3GEP protein, truncations and point mutations of this GEF were performed and they were tested in cell based assays (using melanocytes with Rab3GEP knock out) and in pull down assays (using the capacity to activate Rab27a as a read out of the GEF activity). Moreover, Rab3GEP wild type, and some mutants were mis-targeted from the cytosol (normal localisation) to mitochondria, in order to investigate their capacity to rescue melanosome distribution in melan-Rab3GEP KO cells and to examine their ability to re-target Rab27a to a different membrane organelle. Results reported in this thesis indicate that point mutations within the DENN domain impair the ability of Rab3GEP to rescue the melanosome disperse distribution and to activate Rab27a in vitro assay, suggesting the crucial role of this domain for the Rab3GEP activity. However, the DENN domain alone is not sufficient to rescue melanosome distribution and to activate Rab27a. This suggests an essential role of the other parts of the protein. Moreover, evidence in this thesis indicate that the cytosolic localisation of Rab3GEP is essential for the ability of Rab3GEP to rescue melanosome distribution, and that the targeting activity of Rab3GEP towards Rab27a is dependent on its GEF activity. However, evidence obtained by studying melan-Rab3GEP KO cells indicate that despite the important role of Rab3GEP in Rab27a activation/targeting, it is not essential.